Peningkatan Kandungan Organosulfur Umbi Bawang Putih (Allium sativum L.) Dengan Pemupukan Super Fosfat dan Belerang - Ihsan, Mohamad; Rachmawatie, Srie Juli; Muthoharri, Hariri; Husna, Arifah (Universitas Sebelas Maret, 2025)
Garlic has been recognized as a medicinal plant. The most efficacious part of garlic is the bulb, because it contains the compound allicin, a substance that functions as an antibiotic and can boost the immune system. Allicin is an organosulfur compound. This study aims to examine the effect of sulfur application on increasing organosulfur content in garlic plants cultivated with phosphate fertilization. This study used a factorial Randomized Complete Group Design (RCGD), consisting of two treatment factors, which are the provision of phosphate fertilizer in three levels (S1: SP-36 150 kg/ha, S2: SP-36 200 kg/ha, S3: SP-36 250 kg/ha) and sulfur fertilizer in three levels (B1: 40 kg/ha, B2: 80 kg/ha, B3: 120 kg/ha). From the experiment, the results showed that the application of sulfur had a very significant effect on plant height and number of leaves and gave differences in organosulfur content in tubers although not significant. There was also no significant difference in the application of phosphate fertilizer and sulfur on organosulfur content in garlic bulbs. The highest organosulfur content in the bulbs was 341.12 mg/kg obtained in the treatment of SP-36 150 kg/ha and sulfur as much as 80 kg/ha.